Neutrophil-to-lymphocyte ratio and stenosis severity in ischemic stroke: Digital subtraction angiography evaluation and implications for inflammation-based risk stratification in the Indonesian population - Fiqri, Aidil; Musadir, Nasrul; Imran, Imran; Desiana, Desiana; Hastuti, Sri (Narra Sains Indonesia, 2025)
Neutrophil-to-lymphocyte ratio (NLR), an accessible biomarker derived from routine blood counts, has been associated with stroke severity and outcomes. However, its association with angiographically confirmed stenosis has not been fully established. The aim of this study was to investigate the correlation and association between the NLR and the severity of intracranial arterial stenosis assessed by digital subtraction angiography (DSA). An observational analytic study with a cross-sectional design was conducted. Patients with acute ischemic stroke who underwent DSA were included using a total sampling method. Eligible patients were aged >18 years, had ischemic stroke onset <14 days, and had no prior thrombolysis, endovascular treatment, or surgery for cerebral stenosis. Those with infection, hematological disorders, malignancy, or immunosuppression were excluded. NLR was calculated from complete blood count results at admission, while stenosis severity was quantified using the Warfarin–Aspirin Symptomatic Intracranial Disease (WASID) method. A total of 44 ischemic stroke patients who underwent DSA were included. Pearson correlation test revealed a strong positive correlation between NLR and the severity of intracranial arterial stenosis (r=0.671; p<0.001). In subgroup analysis, NLR showed a strong positive correlation with stenosis severity in the cerebral arteries (r=0.707; p<0.001), but not in the carotid arteries (r=0.434; p=0.182). One-way ANOVA revealed significant differences in NLR across stenosis severity groups (p<0.0001), with higher NLR in moderate and severe stenosis compared with mild stenosis (p=0.017 and p=0.0003, respectively). These findings suggest that NLR reflects the inflammatory burden contributing to vascular narrowing and may serve as a simple and widely available biomarker for identifying ischemic stroke patients with a higher burden of intracranial arterial stenosis, particularly in settings where access to advanced imaging is limited.